Dispersive liquid–liquid microextraction based on solidification of floating organic droplet for the determination of triazine and triazoles in mineral water samples. Issue 17 (6th September 2016) - Bolzan, Cátia M.; Caldas, Sergiane S.; Guimarães, Bruno S.; Primel, Ednei G.
Abstract : A simple, rapid, and sensitive method for the determination of atrazine, simazine, cyproconazole, tebuconazole, and epoxiconazole in mineral water employing the dispersive liquid–liquid microextraction with solidification of a floating organic drop with determination by liquid chromatography tandem mass spectrometry has been developed. A mixed solution of 250 μL 1‐dodecanol and 1250 μL methanol was injected rapidly into 10 mL aqueous solution (pH 7.0) with 2% w/v NaCl. After centrifugation for 5 min at 2000 rpm, the organic solvent droplets floated on the surface of the aqueous solution and the floating solvent solidified. The method limits of detection were between 3.75 and 37.5 ng/L and limits of quantification were between 12.5 and 125 ng/L. The recoveries ranged from 70 to 118% for repeatability and between 76 and 95% for intermediate precision with a relative standard deviation from 2 to 18% for all compounds. Low matrix effect was observed. The proposed method can be successfully applied in routine analysis for determination of pesticide residues in mineral water samples, allowing for monitoring of triazine and triazoles at levels below the regulatory limits set by international and national legislations.